Ventricular Fibrillation due to Severe Hypokalemia in a Patient with Thyrotoxic Periodic Paralysis (Annals of Medical Research, 2021)
None
Keywords: Thyrotoxicosis; Hypokalemia; Hypokalemic Periodic Paralysis.